2018
DOI: 10.1126/science.aam9991
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of nonlocal hot-electron energy dissipation via shot noise

Abstract: In modern microelectronic devices, hot electrons accelerate, scatter, and dissipate energy in nanoscale dimensions. Despite recent progress in nanothermometry, direct real-space mapping of hot-electron energy dissipation is challenging because existing techniques are restricted to probing the lattice rather than the electrons. We realize electronic nanothermometry by measuring local current fluctuations, or shot noise, associated with ultrafast hot-electron kinetic processes (~21 terahertz). Exploiting a scann… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
68
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 53 publications
9
68
1
Order By: Relevance
“…In their work, a passive imaging technique was proposed in which the thermal evanescent waves from the sample surface directly provided near‐field interactions with the tip and eventually scattered into the far‐field. Another recent work by Weng et al proposed an s‐SNOM‐based method of imaging nonlocal electron energy dissipation by measuring the local current fluctuations generated by nonequilibrium electrons 4)Furthermore, the current spatial resolution of s‐SNOM is predominantly limited by the curvature radius of the tip apex.…”
Section: Othersmentioning
confidence: 99%
“…In their work, a passive imaging technique was proposed in which the thermal evanescent waves from the sample surface directly provided near‐field interactions with the tip and eventually scattered into the far‐field. Another recent work by Weng et al proposed an s‐SNOM‐based method of imaging nonlocal electron energy dissipation by measuring the local current fluctuations generated by nonequilibrium electrons 4)Furthermore, the current spatial resolution of s‐SNOM is predominantly limited by the curvature radius of the tip apex.…”
Section: Othersmentioning
confidence: 99%
“…In this respect, the study of the second moment M[ji] at arbitrary finite frequency indicated for instance the relevant impact of bound states on the particle transport. This result implies that the recent experimental progress in finite frequency quantum transport can provide a new valuable tool for bound state spectroscopy.…”
Section: Discussionmentioning
confidence: 92%
“…In the context of noise spectroscopy, it was indeed recently suggested that noise may be used to measure electronic temperatures 26,28 . Here, we follow the suggestion of Ref.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Connection between current-induced light emission and electronic shot noise was demonstrated experimentally 24 , and a theory of light emission from quantum noise was formulated 25 . Recently, shot noise was employed to image hot electron energy dissipation 26 , and extract information on the local electronic temperatures 27,28 .…”
Section: Introductionmentioning
confidence: 99%